Phototrophic pigment production with microalgae: biological constraints and opportunities. Issue 2 (15th March 2014) - Mulders, Kim J. M.; Lamers, Packo P.; Martens, Dirk E.; Wijffels, René H.; Bassi, R.
<x xml:space="preserve">Abstract</x> There is increasing interest in naturally produced colorants, and microalgae represent a bio‐technologically interesting source due to their wide range of colored pigments, including chlorophylls (green), carotenoids (red, orange and yellow), and phycobiliproteins (red and blue). However, the concentration of these pigments, under optimal growth conditions, is often too low to make microalgal‐based pigment production economically feasible. In some Chlorophyta (green algae), specific process conditions such as oversaturating light intensities or a high salt concentration induce the overproduction of secondary carotenoids (β‐carotene in Dunaliella salina (Dunal) Teodoresco and astaxanthin in Haematococcus pluvialis (Flotow)). Overproduction of all other pigments (including lutein, fucoxanthin, and phycocyanin) requires modification in gene expression or enzyme activity, most likely combined with the creation of storage space outside of the photosystems. The success of such modification strategies depends on an adequate understanding of the metabolic pathways and the functional roles of all the pigments involved. In this review, the distribution of commercially interesting pigments across the most common microalgal groups, the roles of these pigments in vivo and their biosynthesis routes are reviewed, and constraints and opportunities for overproduction of both primary and secondary pigments are presented.